Margaret O'Mara, The Code. Silicon Valley and the Remaking of America reviewed by Antti Tarvainen. (28th March 2022) - Tarvainen, Antti
Abstract : Silicon Valley has emerged as the key metaphor of the innovation-led economic development in the 21st century. As the Valley's technology monopolies and utopias expand, there is a growing need for critical histories that help to ground and contextualize the futures that are spreading from San Francisco Bay. In this review essay, I suggest that a settler-colonial approach offers interesting possibilities for the creation of such histories. To demonstrate how such an approach works, I develop a settler-colonial reading of Margaret O'Mara's recent book The Code: Silicon Valley and the Remaking of America (2019). By critically analysing the key metaphors in O'Mara's celebrated book, the global and violent face of the Valley becomes visible. The settler-colonial approach, I conclude, offers one possible analytical approach to breaking the stranglehold of America-centred understanding typical of the histories of Valley.